Predictors of 30-Day Mortality in Hospitalized Patients with Clostridium difficile Infection. Issue 8 (August 2017) - Chintanaboina, Jayakrishna; Navabi, Seyedehsan; Suchniak-Mussari, Kristen; Stern, Benjamin; Bedi, Simranjit; Lehman, Erik B.; Tinsley, Andrew
Abstract: Objectives: Clostridium difficile infection (CDI) is a significant cause of morbidity and mortality and is the most common nosocomial infection in the United States, with associated annual costs of approximately $3 billion. The epidemiology of CDI has changed with the identification of novel risk factors for incident and recurrent CDI. The aim of this study was to identify the predictors of 30-day mortality in hospitalized patients with CDI. Methods: We identified all of the patients diagnosed as having CDI from January 2011 to December 2014 at our university-setting hospital. Data were extracted using electronic medical records and chart review. The data of all of the patients who died within 30 days of incident CDI were compared with those who survived beyond 30 days of incident CDI. A multivariable logistic regression model was created for mortality after finding a subset of significant predictor variables by making bivariate comparisons also using logistic regression. Results: A total of 893 patients were diagnosed as having CDI during the study period. The mean age was 62 years and 49.5% were women. The mean length of hospital stay was 11.73 days. Of the 893 patients with CDI, 98 (10.97%) died within 30 days of incident CDI. CDI recurrence was noted in 76 patients (8.51%). On multivariate logistic regression analysis, peptic ulcer disease, advanced age, Charlson comorbidity index, and intensive care unit status were found to be significantly associated with 30-day mortality. There was no significant association between acid suppression and CDI mortality. Conclusions: Advanced age, Charlson comorbidity index, intensive care unit status, and peptic ulcer disease are predictors of all-cause 30-day mortality in hospitalized patients with CDI. Abstract : Clostridium difficile infection (CDI) in hospitalized patients is a significant healthcare burden in the United States. The incidence of CDI has increased significantly during the last decade despite treatment guidelines and preventive measures. The risk factors for the occurrence of CDI are already known. This article focuses on the predictors of 30-day mortality in hospitalized patients with CDI.